Incidence of cardiovascular events in patients with stabilized coronary heart disease: the EUROASPIRE IV follow-up study - De Bacquer, Dirk; De Smedt, Delphine; Kotseva, Kornelia; Jennings, Catriona; Wood, David; Rydén, Lars; Gyberg, Viveca; Shahim, Bahira; Amouyel, Philippe; Bruthans, Jan; Castro Conde, Almudena; Cífková, Renata; et al. (European journal of epidemiology, 2019)
The EUROASPIRE surveys (EUROpean Action on Secondary Prevention through Intervention to Reduce Events) demonstrated that most European coronary patients fail to achieve lifestyle, risk factor and therapeutic targets. Here we report on the 2-year incidence of hard cardiovascular (CV) endpoints in the EUROASPIRE IV cohort. EUROASPIRE IV (2012-2013) was a large cross-sectional study undertaken at 78 centres from selected geographical areas in 24 European countries. Patients were interviewed and examined at least 6 months following hospitalization for a coronary event or procedure. Fatal and non-fatal CV events occurring at least 1 year after this baseline screening were registered. The primary outcome in our analyses was the incidence of CV death or non-fatal myocardial infarction, stroke or heart failure. Cox regression models, stratified for country, were fitted to relate baseline characteristics to outcome. Our analyses included 7471 predominantly male patients. Overall, 222 deaths were registered of whom 58% were cardiovascular. The incidence of the primary outcome was 42 per 1000 person-years. Comorbidities were strongly and significantly associated with the primary outcome (multivariately adjusted hazard ratio HR, 95% confidence interval): severe chronic kidney disease (HR 2.36, 1.44-3.85), uncontrolled diabetes (HR 1.89, 1.50-2.38), resting heart rate ≥ 75 bpm (HR 1.74, 1.30-2.32), history of stroke (HR 1.70, 1.27-2.29), peripheral artery disease (HR 1.48, 1.09-2.01), history of heart failure (HR 1.47, 1.08-2.01) and history of acute myocardial infarction (HR 1.27, 1.05-1.53). Low education and feelings of depression were significantly associated with increased risk. Lifestyle factors such as persistent smoking, insufficient physical activity and central obesity were not significantly related to adverse outcome. Blood pressure and LDL-C levels appeared to be unrelated to cardiovascular events irrespective of treatment. In patients with stabilized CHD, comorbid conditions that may reflect the ubiquitous nature of atherosclerosis, dominate lifestyle-related and other modifiable risk factors in terms of prognosis, at least over a 2-year follow-up period.
Keywords: mužské pohlaví; Male; Coronary Disease; senioři; Female; Humans; následné studie; lidé; Follow-Up Studies; Cross-Sectional Studies; Middle Aged; ženské pohlaví; lidé středního věku; Evropa; kardiovaskulární nemoci; rizikové faktory; Life Style; životní styl; koronární nemoc; Europe; Risk Factors; incidence; průřezové studie; Aged; Incidence; Cardiovascular Diseases